Desenvolvimento de modelo conceitual para concepção de projetos para desconstrução - Spadotto, Aryane (2022)
In civil construction, the demolition process has evolving from the concern with environmental issues and the ideology of sustainability. As an alternative to minimize the generation of construction and demolition waste (CDW) and reduce the consumption of raw materials, was born the concept of project for deconstruction (PpD). This process enables the reuse and/or recycling of materials and components. Considering that the lack of specific parameters for deconstruction based on construction processes is a barrier for professionals to apply this concept, the research aims to develop a conceptual model that can be used as a guideline in the design phase of construction projects. Buildings and that enables the deconstruction process. For the development of this study, bibliographic and documentary research was carried out with the survey of articles and scientific information, as well as documents, guides with guidelines and principles for the project for deconstruction, in addition to legal and political strategies used in different countries. From this survey, principles of five guides for deconstruction in force in other countries were selected, considering the criteria of relevance and actuality. In the development of the predictive conceptual model, the research method used was Design Science Research, which involves a definition of a solution to problems with the creation of artifacts. For the development of the conceptual model, as defining 71 guidelines defined on materials used in civil construction, as requirements defined by similarity later, as terminology, constructive techniques and materials used in construction were considered, as normative requirements of international and identification certificates of items in environmental certificates, which resulted in the proposition 8 guidelines. For the validation of each guideline proposed in the PpD model, estimates were made regarding usability and applicability. From the comparisons and verifications, the proposal of the conceptual model of PpD is composed of eight guidelines. The model of this reading was conceived by the strategy and its use in an inspired way to simplify the project and favor the use of PpD strategies, as well as facilitate the projects identification of requirements and use, and collaborating to disseminate this strategy in building. Its intention to present a viable research application is useful, in addition, to contribute to prolong the useful life of buildings and minimize the generation of CDW and environmental impacts.